RETRACTED ARTICLE: Embelin alleviates weaned piglets intestinal inflammation and barrier dysfunction via PCAF/NF-κB signaling pathway in intestinal epithelial cells - Weilei Yao; Tongxin Wang; Lu Huang; Zhengxi Bao; Shu Wen; Feiruo Huang (Journal of Animal Science and Biotechnology)
Abstract Background Intestinal barrier plays key roles in maintaining intestinal homeostasis. Inflammation damage can severely destroy the intestinal integrity of mammals. This study was conducted to investigate the protective effects of embelin and its molecular mechanisms on intestinal inflammation in a porcine model. One hundred sixty 21-day-old castrated weaned pigs (Duroc × Landrace × Yorkshire, average initial body weight was 7.05 ± 0.28 kg, equal numbers of castrated males and females) were allotted to four groups and fed with a basal diet or a basal diet containing 200, 400, or 600 mg embelin/kg for 28 d. The growth performance, intestinal inflammatory cytokines, morphology of jejunum and ileum, tight junctions in the intestinal mucosa of piglets were tested. IPEC-1 cells with overexpression of P300/CBP associating factor (PCAF) were treated with embelin, the activity of PCAF and acetylation of nuclear factor-κB (NF-κB) were analyzed to determine the effect of embelin on PCAF/NF-κB pathway in vitro. Results The results showed that embelin decreased (P < 0.05) serum D-lactate and diamine oxidase (DAO) levels, and enhanced the expression of ZO-1, occludin and claudin-1 protein in jejunum and ileum. Moreover, the expression levels of critical inflammation molecules (interleukin-1β, interleukin-6, tumor necrosis factor-α, and NF-κB) were down-regulated (P < 0.05) by embelin in jejunal and ileal mucosa. Meanwhile, the activity of PCAF were down-regulated (P < 0.05) by embelin. Importantly, transfection of PCAF siRNAs to IPEC-1 cell decreased NF-κB activities; embelin treatment downregulated (P < 0.05) the acetylation and activities of NF-κB by 31.7%–74.6% in IPEC-1 cells with overexpression of PCAF. Conclusions These results suggested that embelin ameliorates intestinal inflammation in weaned pigs, which might be mediated by suppressing the PCAF/NF-κB signaling pathway.